HUKUM MENYEDIAKAN KONSUMSI KEPADA DOSEN PADA SIDANG TUGAS AKHIR: Dalam Tinjauan Hukum Positif Dan Hukum Islam - Abdillah, Muhammad Torieq; Parahdina, Soraya; Fatmawati, Amelia; Vijaini, Akhmad; Habibah, Nor (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2025)
Abstract: The provision of food and beverages to examiners during undergraduate thesis defenses is a common practice in academic settings, often regarded as a gesture of appreciation or respect by students. However, this practice raises ethical and legal concerns, particularly regarding its potential classification as gratification that could influence the objectivity of academic assessment. This study aims to examine the legal status of such practices from the perspectives of positive law and Islamic law, and to assess the extent to which this tradition is normatively and ethically acceptable. The research employs a normative legal method, incorporating statutory, comparative, and conceptual approaches. Data sources include statutory regulations, religious fatwas, and scholarly literature. The findings indicate that, under positive law, the provision of food may constitute gratification if intended to influence academic decisions; however, it does not necessarily violate the law if done sincerely and within reasonable limits. From the perspective of Islamic law, such acts are permissible as long as they do not involve elements of risywah (bribery) or raise suspicion. Therefore, it is essential for higher education institutions to establish clear ethical guidelines to uphold academic integrity amidst evolving traditions of reciprocal social gestures.